Effects Mixture Powder of Black Rice, Red Beans and Moringa Leaves on Blood Glucose in Hyperglycemic Rats - Lalu Juntra Utama (Journal of Global Pharma Technology, 2020)
Introduction: The increase in blood sugar or hyperglycemia is a metabolic disorder known as diabetes mellitus and is associated with the rise of oxidative stress and complications in the vascular system. Further, it will cause alteration in carbohydrate and fat metabolism leads to a reduction of the antioxidant defense system. Black rice, red beans and moringa leaves contain oleic acid, butyric amino acid, antioxidants, phytic acid and arginine which can improve insulin sensitivity and blood glucose homeostatis. This study aims to identify the effect of mixture powder (black rice, red beans, and moringa leaves) based feeding against the blood glucose level in rats. Methods: The study was an experimental research with pre and post control group design. A total of 20 Sprague Dawley female rats were divided into four groups, namely standard feed (PS), 80% mixture powder feeding (PB8), 50% mixture powder feeding (PB5) and 20% mixture powder feeding (PB2). The mixture powder intervention was executed about 5% of body weight for 28 days. Fasting blood glucose was measured using the GOD-PAP method. The data obtained was conducted the statistical analysis using the Analysis of Variance (ANOVA) at a 95% confidence level. If it showed a significant effect on the response variable, then Duncan's Multiple Range Test would be conducted. Results: There were significant differences in fasting blood glucose among groups after the mixture powder intervention. The results revealed that after 28 days, mixture powder might lower the serum glucose concentration from 122.69 mg/dL to 97.70 mg/dL (20.37%) in the PB8 group and from 123.91 mg/dL to 113.28 mg/dL (8.58%) in the PB5 group, but vice versa, the blood glucose in the PS group, intervened by standard-based feeding increased by 5.73%. According to these results, mixture powder can be considered to reduce blood glucose in people with obesity and metabolic syndrome. Conclusion: The intervention of a mixture of black rice, red beans, and Moringa leaves may significantly influence the fasting blood glucose in rats. Keywords: Black rice, red beans, moringa leaves, fasting blood glucose